EPOR2/βcR2-independendent effects of low-dose epoetin-α in porcine liver transplantation. Issue 6 (5th December 2017) - Kebschull, Linus; Theilmann, Leon Franz Christoph; Mohr, Annika; Uennigmann, Wencke; Stoeppeler, Sandra; Heitplatz, Barbara; Spiegel, Hans-Ullrich; Bahde, Ralf; Palmes, Daniel Michael; Becker, Felix
Abstract : Ischemia–reperfusion injury (IRI) remains a key component of graft damage during transplantation. Erythropoietin (EPO) induces anti-inflammatory and anti-apoptotic effects via the EPOR2 /βcR2 complex, with a potential risk of thrombosis. Previous work indicates that EPO has EPOR2 /βcR2 -independent protective effects via direct effects on the endothelium. As the EPOR2 /βcR2 receptor has a very low affinity for EPO, we aimed to test the hypothesis that EPO doses below the level that stimulate this receptor elicit cytoprotective effects via endothelial stimulation in a porcine liver transplantation model. Landrace pigs underwent allogenic liver transplantation (follow-up: 6 h) with a portojugular shunt. Animals were divided into two groups: donor and recipient treatment with low-dose EPO (65 IU/kg) or vehicle, administered 6 h before cold perfusion and 30 min after warm reperfusion. Fourteen of 17 animals (82.4%) fulfilled the inclusion criteria. No differences were noted in operative values between the groups including hemoglobin, cold or warm ischemic time. EPO-treated animals showed a significantly lower histopathology score, reduced apoptosis, oxidative stress, and most important a significant up-regulation of endothelial nitric oxide (NO) synthase (eNOS). Donor and recipient treatment with low-dose EPO reduces the hepatic IRI via EPOR2 /βcR2 -independent cytoprotective mechanisms and represents a clinically applicable way to reduce IRI.